(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Charaka Samhita is an ancient Indian medical treatise that has stood the test of time. It covers a vast range of topics from fundamental principles of Ayurveda to the diagnosis, treatment and prevention of diseases. Its Wisdom has inspired generations of scholars and seekers of knowledge, shaping the evolution of Indian thought and culture. In order to attain scientific knowledge, three different means of knowledge (Trividha jnanopaya) are mentioned in Charaka Samhita. It includes Adhyayana (learning), Adhyapana (teaching) and Tadvidya-Sambhasha (discussions and debates). Among them, Tadvidhyasambhasha plays an important role in shaping the current form of Charaka Samhita making it accurate by rectifying the mistakes. This article is intended for analyzing various instances of Tadvidya-Sambhasha and their outcomes in Charaka Samhita.